Analisis Persepsi Terhadap Teknologi Augmented Reality Dalam Kegiatan Pembelajaran Di Kota Jambi Menggunakan Technology Acceptance Model (TAM) (Studi Kasus : SD, SMP, SMA ATTAUFIQ) - Muhammad Fahmi1, Said; Jasmir; Rianti Agustini, Silvia (Jurnal Informatika Dan Rekayasa Komputer(JAKAKOM), 2024)
Technology is something that has always been and will continue to evolve along with the times. Increasingly, various kinds of new technologies are emerging. This study aims to analyze the perception of using Augmented Reality technology in learning. The measurement model that will be used in this study is the Technology Acceptance Model (TAM) developed by Davis. this Research has 3 hypotheses. The model and hypotheses are validated through online questionnaires. looked at 72 teacher respondents at Attaufiq Elementary School, Middle School, and High School, Jambi City. The research data was processed using the Structural Equation Model (SEM) method through SmartPLS version 3 software. The results showed that Perceived Convenience had a significant effect on the Attitude variable with t-statistics > t-table value, namely 4,934 > 1.96, Perceived Range had a significant effect on Attitude variable with t-statistics > t-table value, namely 2,647 > 1 .96, and Attitude has a significant effect on the Intention to use variable with t-statistics > t-table value, namely 2,599 > 1.96.